Investments : analysis and behavior - Hirschey, Mark.; Nofsinger, John R. (Boston : McGraw-Hill Irwin, 2008)
This book provides students with knowledge of investment analytical tools and an understanding of the forces that drive the industry. Including Market efficiency and investor behavior, market anomalies and financial statement analysis
Part 1: Introduction to Investments 1 Introduction 2 Equity Markets 3 Buying and Selling Equities 4 Risk and Return Part 2: Market Efficiency and Investor Behavior 5 Asset Pricing Theory and Performance Evaluation 6 Efficient-Market Hypothesis 7 Market Anomalies 8 Psychology and the Stock Market Part 3: Investment Analysis 9 Business Environment 10 Financial Statement Analysis 11 Value-Stock Investing 12 Growth-Stock Investing 13 Technical Analysis Part 4: Fixed Income 14 Bond Instruments and Markets 15 Bond Valuation Part 5: Investment Management 16 Mutual Funds 17 Global Investing 18 Option Markets and Strategies 19 Futures Markets 20 Real Estate and Tangible Assets Appendix A: The Time Value of Money and Compounding Appendix B: Chartered Financial Analyst Questions Glossary Index
Includes bibliographical references and index.
eng.
Keywords: Investments